The effect of low-intensity resistance training after heat stress on muscle size and strength of triceps brachii: a randomized controlled trial - Nakamura, Masatoshi (BMC Musculoskelet Disord, 2019)
BACKGROUND: The purpose of this study was to clarify whether there is a synergistic effect on muscular strength and hypertrophy when low-intensity resistance training is performed after heat stress. METHODS: Thirty healthy young male volunteers were randomly allocated to either the low-intensity resistance training with heat stress group or the control group. The control group performed low-intensity resistance training alone. In the low-intensity resistance training with heat stress group, a hot pack was applied to cover the muscle belly of the triceps brachii for 20 min before the training. The duration of the intervention was 6 weeks. In both groups, the training resistance was 30% of the one repetition maximum, applied in three sets with eight repetitions each and 60-s intervals. The one repetition maximum of elbow extension and muscle thickness of triceps brachii were measured before and after 6 weeks of low intensity resistance training. RESULTS: There was no significant change in the one-repetition maximum and muscle thickness in the control group, whereas there was a significant increase in the muscle strength and thickness in the low-intensity resistance training with heat stress group. CONCLUSION: The combination of heat stress and low-intensity resistance training was an effective method for increasing muscle strength and volume. TRIAL REGISTRATION: University Hospital Medical Information Network Clinical Trials Registry (UMIN000036167; March 11, 2019).